Application of MR diffusion imaging for non-invasive assessment of acute kidney injury after lung transplantation. Issue 49 (4th December 2020) - Derlin, Katja; Hellms, Susanne; Gutberlet, Marcel; Peperhove, Matti; Jang, Mi-Sun; Greite, Robert; Hartung, Dagmar; Derlin, Thorsten; Fegbeutel, Christine; Tudorache, Igor; Jüttner, Björn; Wiese, Birgitt; et al.
Abstract : Abstract: To assess whether MR diffusion imaging may be applied for non-invasive detection of renal changes correlating with clinical diagnosis of acute kidney injury (AKI) in patients after lung transplantation (lutx). Fifty-four patients (mean age 49.6, range 26–64 years) after lutx were enrolled in a prospective clinical study and underwent functional MR imaging of the kidneys in the early postoperative period. Baseline s-creatinine ranged from 39 to 112 μmol/L. For comparison, 14 healthy volunteers (mean age 42.1, range 24–59 years) underwent magnetic resonance imaging (MRI) using the same protocol. Renal tissue injury was evaluated using quantification of diffusion and diffusion anisotropy with diffusion-weighted (DWI) and diffusion-tensor imaging (DTI). Renal function was monitored and AKI was defined according to Acute-Kidney-Injury-Network criteria. Statistical analysis comprised one-way ANOVA and Pearson correlation. 67% of lutx patients (36/54) developed AKI, 47% (17/36) had AKI stage 1, 42% (15/36) AKI stage 2, and 8% (3/36) severe AKI stage 3. Renal apparent diffusion coefficients (ADCs) were reduced in patients with AKI, but preserved in transplant patients without AKI and healthy volunteers (2.07 ± 0.02 vs 2.18 ± 0.05 vs 2.21 ± 0.03 × 10 –3  mm 2 /s, P  < .05). Diffusion anisotropy was reduced in all lutx recipients compared with healthy volunteers (AKI: 0.27 ± 0.01 vs no AKI: 0.28 ± 0.01 vs healthy: 0.33 ± 0.02; P  < .01). Reduction of renal ADC correlated significantly with acute loss of renal function after lutx (decrease of renal function in the postoperative period and glomerular filtration rate on the day of MRI). MR diffusion imaging enables non-invasive assessment of renal changes correlating with AKI early after lutx. Reduction of diffusion anisotropy was present in all patients after lutx, whereas marked reduction of renal ADC was observed only in the group of lutx recipients with AKI and correlated with renal function impairment. Abstract : Supplemental Digital Content is available in the text